2018
DOI: 10.1248/cpb.c18-00381
|View full text |Cite
|
Sign up to set email alerts
|

Manganese-Catalyzed Oxophosphorylation Reaction of Carbon–Carbon Double Bonds Using Molecular Oxygen in Air

Abstract: A novel aerobic manganese-catalyzed oxophosphorylation reaction of carbon-carbon double bonds of styrene derivatives and vinyl ethers using diethyl H-phosphonates was developed. This direct transformation of alkenes to β-ketophosphonate readily proceeded at room temperature via the direct incorporation of molecular oxygen present in air (open flask).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Meanwhile, Chen and Zhao [8] found that the single copper salt could catalyze the oxophosphorylation reaction of α , β ‐alkenyl carboxylic acids or styrenes with H‐phosphonates under air atmosphere. Also, Makino group [9] realized such catalytic process at room temperature by using Mn(acac) 3 as a catalyst. Although these difunctionalization protocols allowed the construction of β ‐ketophosphonates from readily available starting materials, they usually relied on the catalytic activity of copper or manganese metals.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, Chen and Zhao [8] found that the single copper salt could catalyze the oxophosphorylation reaction of α , β ‐alkenyl carboxylic acids or styrenes with H‐phosphonates under air atmosphere. Also, Makino group [9] realized such catalytic process at room temperature by using Mn(acac) 3 as a catalyst. Although these difunctionalization protocols allowed the construction of β ‐ketophosphonates from readily available starting materials, they usually relied on the catalytic activity of copper or manganese metals.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, Yamamoto–Makino's group extended the scope of alkenes to vinyl ethers. 24 Thus, several alkyl/aryl 2-(diethoxyphosphoryl)acetates 21 were synthesized in moderate yields, ranging from 42% to 57%, via the Mn(acac) 3 -catalyzed oxyphosphorylation of corresponding vinyl ethers 19 with dimethyl phosphonate 20 and O 2 in MeCN at room temperature ( Scheme 8 ). Noteworthy, Mn(acac) 2 was also found to promote this transformation; albeit, at lower efficiency.…”
Section: Oxyphosphorylation Of Alkenesmentioning
confidence: 99%